PARALLELS OF SCHOOL CHILDREN’S AND STUDENTS’ LEARNING TO LEARN COMPETENCE - Pukevičiūtė, Virginija Jūratė (Acta Paedagogica Vilnensia, 2010)
A noticeable interest has been observed in the formation of learning to learn competence in both the documents of educational policy and in scientific sources, where the importance of this process is highlighted, which is treated as a lifelong learning activity. Therefore, the need to reveal different learners’ ability and preparation to learn how to learn becomes comprehensible. Thus the research problem could be expressed by the question if there exists differences between higher grade schoolchildren’s and first year students’ learning to learn competence, what complementary parts of this competence are more developed within the two groups of the respondents.To fulfill the objective of the research – to reveal and to compare the level of learning to learn competence of higher grade schoolchildren and first year students, the following research tasks have been defined: 1) to determine differences between schoolchildren’s and students’ competence of planning and evaluation of learning 2) to analyze the priorities of organizing learning of both groups of respondents 3) to reveal differences of the respondents’ viewpoints on the perception of the importance of learning to learn and emotional learning experience.The research data revealed some statistically relevant differences between the development of schoolchildren’s and students’ learning to learn competence, although in the author’s opinion these differences do not have essential influence on the development of this competence. Most significant changes were determined in the schoolchildren’s and students’ ability to organize learning. Students’ priorities are evident: creation of a suitable learning environment and preparation for learning. Besides, it became obvious that schoolchildren are better at applying various communication forms in learning. It has become clear that students are able to have a deeper insight into personal importance of learning, whereas schoolchildren demonstrated higher self-confidence and courage to communicate in a foreign language.
Keywords: learning to learn; assessment; competencies; schoolchildren; students; differences